Potential use of olive pomaces from Galega Vulgar and Cobrançosa cultivars to obtain phenolic compounds and oligosaccharides with prebiotic activity - Freitas, Laura Anaísa (2022)
Mestrado em Engenharia Alimentar / Instituto Superior de Agronomia. Universidade de Lisboa